The German dual VET System and approaches to enhance employer engagement - Pinnow, Sarah [Verfasser] (My University, 2019)
„VET plays a vital role in equipping the youth of a country with skills for employability, which employers profit from in terms of a skilled workforce, a key for productivity. A well-functioning VET system is a prerequisite; one example is the German dual VET system. In this article, major stakeholders, institutions and legal frameworks that contribute towards the success of dual VET are described. Moreover, the basic aspects of the two learning venues - training at the company and the vocational school - as well as the different motivations to engage in VET are outlined, considering the perspectives of the industry, government and apprentice. In order to facilitate the competence development of the apprentices, a second learning venue in an authentic work environment at the company is needed besides the vocational education and training at the vocational schools. However, industry involvement often poses a major problem. Research projects that focus on the needs of the industry in the dual VET system and other approaches to enhance employer engagement based on related resulting benefits for the industry will be discussed.” (authors’ abstract; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 3.2 Unternehmen und Behörden; 370; Berufsbildungssystem; Duales System; Lernort Betrieb; Ausbildungsverhalten; Bildungstransfer; Sozialpartner; Arbeitgeber